2009
DOI: 10.1021/ie801341j
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Mutual Solubility in the NH4VO3−NH4NO3−H2O system

Abstract: The solubilities of ammonium vanadate and ammonium nitrate in the NH4VO3−NH4NO3−H2O system were investigated at 293, 303, 313, and 323 K by the method of isothermal saturation of solutions. A section of the solubility isotherm for the investigated system was plotted based on the obtained data. Knowledge of that dependence is necessary for developing the new method of using the postfiltration liquor from the soda−chlorine−saltpeter (SCS) method of sodium carbonate production, based on an equilibrium plot for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 8 publications
1
23
0
Order By: Relevance
“…The dependence between the system’s properties, i.e., the densities and the chemical compositions of the equilibrium solutions, was used to determine the number of solid phases in the studied system (Figure ). Points of discontinuity of the function on the curves mark new solid phases formed in the studied system. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The dependence between the system’s properties, i.e., the densities and the chemical compositions of the equilibrium solutions, was used to determine the number of solid phases in the studied system (Figure ). Points of discontinuity of the function on the curves mark new solid phases formed in the studied system. …”
Section: Resultsmentioning
confidence: 99%
“…Comparison of Solubility Data Presented in ThisWork with the Literature Data for the Binary System NH 4 NO 3 −H 2 O6,11,12 …”
mentioning
confidence: 94%
“…For mutual solubility for ternary systems on the 293.15–323.15 K temperature range published data are incomplete. Satisfactory data were found only for the systems: KVO 3 –NH 4 VO 3 –H 2 O and NH 4 VO 3 –NH 4 NO 3 –H 2 O . Data for the KNO 3 –KVO 3 –H 2 O system and the four-component NH 4 NO 3 –KVO 3 –H 2 O do not exist.…”
Section: Introductionmentioning
confidence: 89%
“…) content in the solution was determined using a standard manganometric method involving the titration of oxalate ions against permanganate solution. 21 For this purpose, a sample of the solution (1 mL) was withdrawn, diluted with water to 10 mL, acidified to pH 1 using 1 M H 2 SO 4 , heated to ∼343 K, and titrated against KMnO 4 to allow calculation of the oxalate content in the sample. The vanadate ion (VO 3…”
Section: Methodsmentioning
confidence: 99%
“…Chen presented the equilibrium results of the NH 4 VO 3 –H 2 O system ranging from 273.15 to 343.15 K . Equilibrium studies for NH 4 HCO 3 –NH 4 VO 3 –H 2 O and (NH 4 ) 2 HCO 3 –NH 4 VO 3 –H 2 O systems, respectively, have been published by Trypuc and Stefanowicz and Yan et al, , whereas the NH 4 HCO 3 –NH 4 VO 3 –H 2 O system has been partly reported by Zhao et al Solubility of the NH 4 VO 3 –NH 4 NO 3 –H 2 O system has been published by Trypuc and Druzynski . Solubility of NH 4 VO 3 in NH 4 H 2 PO 4 –H 2 O and (NH 4 ) 3 PO 4 –H 2 O systems has been published by Ning et al , These results are necessary to determine the optimal conditions for carrying out the ammonium precipitation process.…”
Section: Introductionmentioning
confidence: 99%